REPAIR IN THE DIALOGUE OF FROZEN MOVIE - Masyuni, Ni Nyoman Wulan; Savitri, Putu Weddha; Maharani, Sang Ayu Isnu (LPPM Universitas Dhyana Pura, 2024)
The title of this article is â€œRepair in The Dialogue of Frozen Movieâ€. This article aims to identify and analyze the types of repair and repair operations in the dialogue of Frozen movie. The data was taken from the dialogue in Frozen movie which was downloaded from the internet and the data are in the form of utterances. In the data collection, it used a qualitative method. This article used the theory proposed by Schegloff, Jefferson, and Sacks (1977) to classify the types of repairs and Schegloff (2013) to analyze the repair operations. The result of this research shows that all of the four types of repairs found in the dialogue of Frozen movie, namely self-initiated self-repair, self-initiated other-repair, other-initiated self-repair, and other-initiated other-repair. The result also shows that the repair operations found in this research, namely replacing, inserting, aborting, and recycling.